Soil microbial community structure and catabolic activity are significantly degenerated in successive rotations of Chinese fir plantations - Zeyan Wu (Nature Portfolio, 2017)
Abstract This study examined the hypotheses that soil microbial community composition and catabolic activity would significantly degenerated by consecutive monoculture in Chinese fir plantations. The phospholipid fatty acids (PLFA) and community level physiological profiles (CLPP) methods were used to assess the variations of soil microbial community among the first rotation Chinese fir plantation (FCP), the second rotation plantation (SCP) and the third rotation plantation (TCP). The total content of PLFA biomarkers was highest in FCP, followed by SCP, and TCP was the least detected. Conversely, the fungi/bacteria ratio significantly increased in the SCP and TCP soils. The average well-color development (AWCD) values significantly decreased (FCP > SCP > TCP). However, the sum of AWCD values of amino acids, carboxylic acids and phenolic compounds were higher significantly in the SCP and TCP soils than FCP soils, suggesting that the microflora feeding on acids gradually became predominant in the continuous monoculture plantation soils. Soil C/N ratio was one of the most important factors to soil microbial diversity. Both the PLFA and CLPP results illustrated the long-term pure plantation pattern exacerbated the microecological imbalance in the rhizospheric soils of Chinese fir, and markedly decreased the soil microbial community diversity and metabolic activity.